Widely targeted metabolomics analysis of Sanghuangporus vaninii mycelia and fruiting bodies at different harvest stages - Qi, Yue; Guo, Xiao-Ying; Xu, Xin-Yue; Hou, Jian-Xuan; Liu, Shi-Lai; Guo, Hong-Bo; Xu, Ai-Guo; Yang, Rui-Heng; Yu, Xiao-Dan (Frontiers in Microbiology, 2024)
Sanghuangprous vaninii is a medicinal macrofungus cultivated extensively in China. Both the mycelia and fruiting bodies of S. vaninii have remarkable therapeutic properties, but it remains unclear whether the mycelia may serve as a substitute for the fruiting bodies. Furthermore, S. vaninii is a perennial fungus, with therapeutic components that vary greatly depending on the growing year of the fruiting bodies. Hence, it is critical to select an appropriate harvest stage of S. vaninii fruiting bodies for a specific purpose. With the aid of TCMSP, metabolomics based on ultra-high performance liquid chromatography coupled to triple quadrupole mass spectrometry (UHPLC-QQQ-MS) was used to preliminarily determine 81 key active metabolites and 157 active pharmaceutical metabolites for six major diseases-resistance in S. vaninii. To evaluate the substitutability of the mycelia and fruiting bodies of S. vaninii and select an appropriate harvest stage for the fruiting bodies of S. vaninii, we analyzed the metabolite differences, especially active metabolite differences, among the mycelia and fruiting bodies during three different harvest stages (one-year-old, two-year-old, and three-year-old). Moreover, we also determined the most iconic and crucial metabolites in each sample of S. vaninii. These results suggested that the mycelia show promise as a substitute for the fruiting bodies of S. vaninii, and that lengthening the growth year do not necessarily lead to higher accumulation levels of active metabolites in the S. vaninii fruiting bodies. This study provided a theoretical basis for developing and utilizing S. vaninii.